Metastatic seminoma with isolated gastric metastases: a case report. Issue 4 (November 2019) - McLaren, A; Baxter, MA; Katbeh, T; Lynch, V; Fullarton, G; White, J
Gastric metastases are a rare occurrence in patients with malignancy. In case reports of these arising from germ cell tumours, the majority were non-seminomatous germ cell tumours and had evidence of retroperitoneal involvement. We present a unique case of a 67-year-old man with metastatic testicular pure seminoma. He presented with dyspepsia and investigation found isolated metastases to the gastric mucosa and sub-mucosa from a right testicular primary. No lymph node involvement was identified. The patient was managed with curative intent with total gastrectomy and inguinal orchidectomy. To date, there is no evidence of disease recurrence.